2022
DOI: 10.1177/18333583221124371
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of comorbidities of stroke collected in administrative data, surveys, clinical trials and cohort studies

Abstract: Background Administrative data are used extensively for research purposes, but there remains limited information on the quality of these data for identifying comorbidities related to stroke. Objective To compare the prevalence of comorbidities of stroke identified using International Classification Diseases, Australian Modification (ICD-10-AM) or Anatomical Therapeutic Chemical codes, with those from (i) self-reported data and (ii) published studies. Method The cohort included patients with stroke or transient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 22 publications
(25 reference statements)
0
10
0
Order By: Relevance
“…Comorbidities with low sensitivity in the coded hospital data (eg, hypertension) were supplemented using pharmaceutical dispensing records of relevant medications based on Anatomical Therapeutic Chemical codes. 14 Comorbidities were also combined to derive a weighted Charlson comorbidity index score. 15,16 The regularity of primary care physician visits was calculated for the 2 years before stroke using a validated method for persistence.…”
Section: Methodsmentioning
confidence: 99%
“…Comorbidities with low sensitivity in the coded hospital data (eg, hypertension) were supplemented using pharmaceutical dispensing records of relevant medications based on Anatomical Therapeutic Chemical codes. 14 Comorbidities were also combined to derive a weighted Charlson comorbidity index score. 15,16 The regularity of primary care physician visits was calculated for the 2 years before stroke using a validated method for persistence.…”
Section: Methodsmentioning
confidence: 99%
“…For CCs and HIMs , the integrity of clinical documentation is critical for accurate clinical coding. Kilkenny et al (2022) reported variation in the reporting of comorbidities of stroke in administrative data suggesting the need to improve clinical documentation. Duke et al (2022) examined coding-based definitions for sepsis and identified significant differences in sepsis classification in administrative data (e.g.…”
Section: Virtual Special Issue On CDImentioning
confidence: 99%
“…Hosseini et al (2022) argued that data quality enhancement requires collaboration between physicians, nurses, managers and developers of software, suggesting a concept mapping approach to meet this objective. Kilkenny et al (2023) recommended ongoing education for CCs to achieve high-quality coding and more accurate data. Campbell and Giadresco (2020) reviewed 39 articles on computer-assisted clinical coding (CAC) and found it improved both accuracy and quality of data.…”
Section: Virtual Special Issue On CDImentioning
confidence: 99%
See 2 more Smart Citations